Water Chemistry and Nitrogen and Oxygen Isotope Techniques for Tracing Nitrate Sources and Transformation Processes in Ionic Rare Earth Mining Areas - GUO Qiuyan; ZHANG Qiuying; LI Zhao; LI Fadong; WANG Fan (Renmin Zhujiang)
To identify the source,migration and transformation processes,and pollution contribution of nitrate in the water body of ionic rare earth mining areas,this paper determined the anions and nitrate nitrogen-oxygen isotopes of surface and groundwater samples by taking Longnan County as the study area.The results show that the water chemistry type in Longnan County is basically dominated by HCO3·SO4-Ca,and the nitrogen-containing compounds are dominated by nitrate.The characteristic plots of the values of δ15N-NO-3 and δ18O-NO-3 combined with the relationship between NO-3/Cl- molar concentration ratios and Cl- concentrations show that the nitrate concentrations in the Longnan County are mainly influenced by ammonium nitrogen fertilizer,soil nitrogen,manure and mine drainage and that the main process of nitrate transformation is nitrification,with no significant denitrification reactions.The results of the MixSIAR model also show that the nitrate in surface water and groundwater mainly comes from mine drainage,soil nitrogen and manure.